The impact of hepatitis B virus infection status on the prevalence of nonalcoholic fatty liver disease: A population‐based study. Issue 8 (18th November 2019) - Huang, Jiaofeng; Jing, Mengli; Wang, Ciyang; Wang, Mingfang; You, Shunjie; Lin, Su; Zhu, Yueyong
Abstract: Background: We aimed to explore the impact of hepatitis B virus (HBV) infection on the prevalence of nonalcoholic fatty liver disease (NAFLD) based on clinical big data. Methods: Data were collected from the health examination center of the First Affiliated Hospital of Fujian Medical University. Univariate and multivariate analysis were applied to investigate the relationship between HBV and NAFLD. Results: A total of 14 452 patients were included, with an average age of 43.84 ± 13.03 years. Cases of HBV current infection, past infection, and noninfection were 21 102 110 (14.6%), 90 039 003 (62.3%), and 33 393 339 (23.1%), respectively. The prevalence of NAFLD was significantly lower in the current infection group (29.9%) than in the past infection group (35.8%) and noninfection group (31.9%) ( P  < .001). After adjusting for age, the prevalence of NAFLD in the current infection group remained the lowest across all of the age groups. Multivariate analysis showed that current infection was at a lower risk of NAFLD (odds ratio [OR] = 0.717, 95% CI: 0.608‐0.846), whereas past infection had no effect on NAFLD. Conclusions: Current HBV infection may lower the risk of NAFLD. This effect becomes insignificant when the patient is no longer infected.